Multiple struggles in fighting violence against women: implications among Romani women leaders in Spain - Carmen Vives-Cases; Eva Espinar-Ruiz; Esther Castellanos-Torres; Anna-Britt Coe (Taylor & Francis Group, 2017)
Background: Violence against women (VAW) is a central issue in gender studies and one that has united feminist activists from around the world. But this does not mean that this struggle is singular: indeed, one can say that there are many, diverse and sometimes even contradictory struggles occurring throughout the world. Objectives: To identify and analyze the different struggles faced by women from Roma organizations in Spain in relation to VAW and their work with affected women. Methods: Twelve semi-structured interviews were conducted among women actively involved in Roma associations in different Spanish cities, in 2015. An inductive thematic analysis was used to analyze the empirical materials. Results: Our analysis resulted in three themes that captured different struggles that women from Roma organizations have faced: 'between persistence and rupture of restrictive gender norms', 'invisibility and normalization of violence against women' and 'willingness and trust in daily work with women'. The activities related to VAW carried out by the interviewed women were more related to their personal initiatives and abilities than to strategies proposed by the organizations they work for. Conclusions: The results show the need to support the initiatives of Romani women and their own struggles related to identity. This is what makes them true promoters of social change and, more specifically, change related to gender relations both within and outside of their communities.